Testing the Associations Among University Students’ Autonomy, Academic Resilience, and Behavioural Engagement: A Structural Equation Modelling Approach - Trung Kien, Le; Tuan, Duong Minh (Pedagogika, 2025)
This study investigated the interplay among learner autonomy (LA), academic resilience (AR), and behavioural engagement (BE) in tertiary students, focusing on how the components of LA (i.e., independence of learning (IL), study habits (SH)) and AR (i.e., self-determination (SD), adaptability (AD)) influenced BE. The findings revealed significant connections between IL, SD and BE. IL also had a reinforcing link to SD and AD. The association between IL and BE was partially mediated by AR.